A case report of blastic plasmacytoid dendritic cell neoplasm in a hispanic child. (2021) - Tanchiva, Katy Ordoñez; Chavez, Pamela Contreras; Guevara, Silvana Lucero Loli; Vicuña, Carlos Rodrigo Quispe; Bhardwaj, Neharika; Lansigan, Frederick; Deconinck, Erik
Abstract: Plasmacytoid dendritic cell neoplasms are aggressive and rare hematologic malignancies characterized by clonal expansion of plasmacytoid dendritic cells with frequent cutaneous involvement. The pathogenesis is not well established, and it shows enhanced expression of CD56, CD4 and CD123 detected by flow cytometry and immunohistochemistry. We report a case report of this rare disease in a hispanic child with complete remission after using a protocol for high-risk acute lymphoblastic leukemia.